Beispiel Nr: 27
$ \text{Gegeben:} ax^{3}+bx^{2}+cx+d=0 \\ \text{Gesucht:} \\ \text{Lösung der Gleichung} \\ \\ \\ \textbf{Gegeben:} \\ 40\frac{1}{2}x^3+81x^2+40\frac{1}{2}x =0\\ \\ \textbf{Rechnung:} \\ x( 40\frac{1}{2}x^2+81x+40\frac{1}{2})=0 \Rightarrow x=0 \quad \vee \quad 40\frac{1}{2}x^2+81x+40\frac{1}{2}=0\\ \\ 40\frac{1}{2}x^{2}+81x+40\frac{1}{2} =0 \\ x_{1/2}=\displaystyle\frac{-81 \pm\sqrt{81^{2}-4\cdot 40\frac{1}{2} \cdot 40\frac{1}{2}}}{2\cdot40\frac{1}{2}} \\ x_{1/2}=\displaystyle \frac{-81 \pm\sqrt{0}}{81} \\ x_{1/2}=\displaystyle \frac{-81 \pm0}{81} \\ x_{1}=\displaystyle \frac{-81 +0}{81} \qquad x_{2}=\displaystyle \frac{-81 -0}{81} \\ x_{1}=-1 \qquad x_{2}=-1 \\ \underline{x_1=-1; \quad2\text{-fache Nullstelle}} \\\underline{x_2=0; \quad1\text{-fache Nullstelle}} \\$